2019
DOI: 10.1097/fjc.0000000000000646
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Improves Doxorubicin-Induced Cardiac Dysfunction by Modulating Hsp70, Akt, and MAPK Signaling Pathways

Abstract: Atorvastatin is a lipid-regulating drug that is commonly used in clinical practice and can stabilize plaques. Increasing evidence shows that statins have anti–heart failure (HF) effects, but their specific mechanism is not clear. The purpose of this study was to investigate the cardioprotective effects of atorvastatin on HF in rats and its mechanism. Continuous intraperitoneal injection of 2.5 mg/kg/w doxorubicin for 6 weeks, with a cumulative dose of 15 mg/kg, was used to induce a rat model of HF. Then, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…However, pre-incubation with ATV inhibited the TGF-β1-stimulated fibrotic response in hVFs. The results were in agreement with earlier studies, which reported that ATV prevents advanced glycation end products-, angiotensin II-, hypertension-, aldosterone-and doxorubicin-induced cardiac fibrosis (16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, pre-incubation with ATV inhibited the TGF-β1-stimulated fibrotic response in hVFs. The results were in agreement with earlier studies, which reported that ATV prevents advanced glycation end products-, angiotensin II-, hypertension-, aldosterone-and doxorubicin-induced cardiac fibrosis (16)(17)(18)(19)(20).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, statins have also been reported to possess pleiotropic cardiovascular effects, including reduced oxidative stress and inflammation, decreased platelet adhesion, improved endothelial function and enhanced atherosclerotic plaque stability (13)(14)(15). In addition, previous studies have shown that atorvastatin (ATV), a member of the statin family, exerts potential anti-myocardial fibrotic properties (16)(17)(18)(19)(20). Nevertheless, to the best of our knowledge, the molecular mechanism involved in the effect of ATV on cardiac fibrosis remains to be clarified, and limited information is available concerning the possible impact of ATV on TGF-β1-induced human ventricular fibroblast (hVF) proliferation and myofibroblast differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that mitochondrial reactive oxygen species-induced ERK1/2 activation was required for DOX-induced apoptosis and cardiotoxicity [39]. Although there was no direct evidence suggested that the ERK pathway was involved in the DOX-stimulated fibrosis, a couple of studies have shown that treatments that improved cardiac function and reduced myocardial fibrosis were accompanied by decreased phospho-ERK [40,41], which were consistent with our findings. Furthermore, we demonstrated that the increased expression of Sp1 by DOX was ameliorated through exercise intervention.…”
Section: Discussionsupporting
confidence: 91%
“…All data are expressed as the mean ± SD (n = 8). ***p < 0.001 vs C-PN21; ### p < 0.001 vs C-PN90 apoptosis (Gao et al 2018). JNK activation has commonly been associated with cell inflammation and apoptosis, whereas the ERK pathway is implicated in cellular survival and growth (Sun et al 2015b).…”
Section: Discussionmentioning
confidence: 99%